1991
DOI: 10.1002/bms.1200200604
|View full text |Cite
|
Sign up to set email alerts
|

Positive and negative fast atom bombardment mass spectrometry and collision spectroscopy in the structural characterization of mono-, di- and triglycerides

Abstract: The structural characterization of a selection of mono-, di-and triglycerides has been achieved by means of positive and negative ion fast atom bombardment (FAB) mass spectrometry combined with collision experimenh While

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 5 publications
0
13
0
1
Order By: Relevance
“…5) 4 , error 1.11 ppm, RDB 4) if no attention is paid to molecular formula afforded by mass accuracy. Some widespread di-and triglycerides lead to these fragments at m/z 603, 577 and 339, corresponding either to the loss of water, oleoyl, palmitoyl or stearoyl moieties [33]. As it is illustrated in Fig.…”
Section: Hplc-dad-hrms Analysismentioning
confidence: 98%
“…5) 4 , error 1.11 ppm, RDB 4) if no attention is paid to molecular formula afforded by mass accuracy. Some widespread di-and triglycerides lead to these fragments at m/z 603, 577 and 339, corresponding either to the loss of water, oleoyl, palmitoyl or stearoyl moieties [33]. As it is illustrated in Fig.…”
Section: Hplc-dad-hrms Analysismentioning
confidence: 98%
“…Although all these techniques can provide the molecular weight of the intact molecule and some information about the acyl groups, it has not been possible to perform a complete structural determination with mass spectrometry alone. Evans et al (1991) observed that abundant [M Na À R n COOH] and other product ions are formed in the fragmentation of FAB-produced [M Na] ions of triacylglycerols. Some product ions are likely formed by charge-remote fragmentation, although no spectra were shown in their article.…”
Section: Glycolipidsmentioning
confidence: 99%
“…These methods are time‐consuming and cannot confirm the acyl position in TAGs . Mass spectrometry using a variety of ionization techniques has been applied for the characterization of TAGs, including electron impact, chemical ionization, field desorption, desorption chemical ionization, fast atom bombardment (FAB), thermospray, electrospray ionization (ESI), and atmospheric pressure chemical ionization (APCI) . Recently, although structural characterization of regiospecific TAGs by ESI 3 in vegetable oils has been reported, a multilevel MS analysis for completing regiospecific TAGs is still desired .…”
mentioning
confidence: 99%